Functional coating for improving cycle performance of battery, preparation method and application

By using functional coatings formed by polyethylene oxide and bacterial cellulose in lithium metal batteries, the problems of lithium dendrites growth and interface instability are solved, the cycle stability and coulomb efficiency of the battery are improved, and it is suitable for large-scale production. .

CN119220129APending Publication Date: 2024-12-31XI AN JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411387080.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Lithium metal batteries have safety hazards and low Coulomb efficiency due to the uncontrollable growth and interface instability of lithium dendrites, which limit their commercial application. The existing methods are cumbersome and are not suitable for large-scale production.

Method used

Polyethylene oxide and bacterial cellulose are mixed to form functional coatings, dried in vacuum oven and blast oven to form functional coatings containing a large number of polar groups, and applied on copper foil to promote uniform deposition of lithium ions. and inhibit dendrites' growth.

Benefits of technology

It improves the cycle stability and service life of lithium metal batteries, reduces the preparation cost, is suitable for large-scale production, and achieves longer cycle life and higher Coulomb efficiency of lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220129A_ABST
    Figure CN119220129A_ABST
Patent Text Reader

Abstract

The invention discloses a functional coating for improving the cycle performance of a battery as well as a preparation method and application of the functional coating. The functional coating comprises polyoxyethylene, bacterial cellulose and deionized water, the preparation method comprises the following steps: drying polyoxyethylene; adding the dried polyoxyethylene and bacterial cellulose into deionized water, and uniformly mixing the solution to obtain a polyoxyethylene and bacterial cellulose functionalized coating; the method comprises the following steps: placing a functional coating of polyoxyethylene and bacterial cellulose on a copper foil in a dry atmosphere, and uniformly coating the functional coating with a scraper to form a functional coating; the copper foil coated with the functionalized coating is sequentially placed in a blast drying oven and a vacuum drying oven to be dried, and an electrode coated with a polyoxyethylene and bacterial cellulose functionalized coating is obtained; the functional coating can effectively promote uniform deposition of lithium ions and effectively inhibit growth of dendritic crystals, so that the function of prolonging the service life of the lithium metal battery is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery energy storage, and specifically relates to a functionalized coating for improving battery cycle performance, a preparation method and an application thereof. Background Art

[0002] With the development of social economy, the environmental problems and energy crisis caused by the continuous consumption of fossil energy are becoming increasingly prominent, and there is an urgent need to develop new energy storage devices with high energy density, safety and high efficiency. Lithium-ion batteries are widely used in portable electronic devices and electric vehicles due to their high energy density and high output power.

[0003] Lithium metal is known as the "holy grail" among various negative electrode materials for its superior specific capacity and lowest electrode potential standard. However, lithium metal batteries have serious problems such as serious safety hazards caused by uncontrollable growth of lithium dendrites and low coulombic efficiency caused by the high chemical reactivity of lithium metal.

[0004] The formation of lithium dendrites is mainly caused by uneven lithium nucleation and growth. Various factors such as uneven electrode surface, large lithium ion concentration gradient, and uneven surface electronic conductivity may interfere with the uniform deposition of lithium ions, leading to the formation of lithium dendrites. In addition, the solid electrolyte interface layer is another factor that cannot be ignored. If the solid electrolyte interface layer is not flexible enough, it will not be able to prevent dendrite penetration. Dendrite penetration will produce cracks, causing lithium metal to continuously react in the electrolyte, resulting in the continuous formation of a new electrolyte interface layer, which greatly reduces the coulombic efficiency.

[0005] In the process of repeated lithium plating and stripping, the uncontrollable growth of lithium dendrites and unstable interfaces inevitably affect the application of lithium metal batteries, which limits the commercialization of lithium metal negative electrodes to a certain extent. Therefore, it is very important to induce lithium ions to deposit evenly in a certain way during the lithium ion deposition process.

[0006] Meng, J.-K et al. induced uniform deposition of lithium ions by designing carbon cloth with polar groups (Meng, J.-K. et al. Cotton-derived carbon cloth enabling dendrite-free Li deposition for lithium metal batteries. Journal of Power Sources 465, doi: 10.1016 / j.jpowsour.2020.228291 (2020), but this method is cumbersome to operate and is not suitable for large-scale production applications. In addition, the mechanical properties of carbon cloth are poor, which makes the application of this method also have certain limitations. Summary of the invention

[0007] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a functional coating, preparation method and application for improving battery cycle performance, polyethylene oxide, bacterial cellulose and deionized water are mixed to form a functional coating of polyethylene oxide and bacterial cellulose, the functional coating is coated on a copper foil and dried to obtain a functional coating containing a large number of polar groups, the functional coating can effectively promote the uniform deposition of lithium ions and effectively inhibit the growth of dendrites, thereby extending the service life of lithium metal batteries; in addition, the functional coating also has many other advantages, such as light weight, good mechanical properties, and excellent thermal stability; and the preparation method of the functional coating is simple and fast, low cost, and has broad prospects for large-scale production, and the coating uses nano-cellulose with an ultra-fine network structure formed by mutual interweaving, thereby giving the coating excellent mechanical properties and tensile strength.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = (0.5-10): (5-60): (80-120).

[0010] Furthermore, a functionalized coating for improving battery cycle performance includes polyethylene oxide, bacterial cellulose and deionized water; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = (3-4): (15-20): (100-110).

[0011] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0012] Step 1, drying the polyethylene oxide;

[0013] Step 2, adding the polyethylene oxide and bacterial cellulose after the drying treatment in step 1 into deionized water, and stirring to mix the solution evenly to obtain a functional coating of polyethylene oxide and bacterial cellulose;

[0014] The step 1 is specifically as follows:

[0015] The polyethylene oxide is dried in a vacuum oven, the temperature of the vacuum oven is set at 60°C-65°C, and the drying time is 18-26 hours.

[0016] In the step 2, the mass ratio of polyethylene oxide: bacterial cellulose: deionized water is (0.5-10): (5-60): (80-120) or (3-4): (15-20): (100-110).

[0017] In the step 2, a magnetic stirrer is used for stirring, the magnetic stirring rate is 300-600 rpm, and the stirring time is 18-30 hours.

[0018] The invention discloses an application of a functional coating for improving the cycle performance of a battery. The functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil in a dry atmosphere, and is evenly coated with a scraper to form a functional coating; the copper foil coated with the functional coating is placed in a blast oven and a vacuum oven in turn for drying to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating.

[0019] The invention discloses an application of a functional coating for improving the cycle performance of a battery. The functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil in a dry atmosphere, and is evenly coated with a scraper, wherein the thickness of the scraper is 50-400 μm, to form a functional coating; the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 60-80°C for 10-30 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 60-80°C for 18-26 hours, to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 0.1-6 μm.

[0020] A battery comprises an electrode, wherein the electrode is coated with the polyethylene oxide and bacterial cellulose functional coating or an electrode with the polyethylene oxide and bacterial cellulose functional coating prepared by the method.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention achieves the improvement of the stable cycle stability of lithium metal batteries by applying the prepared functionalized coating on the copper foil and drying it. The functionalized coating containing a large number of polar groups can effectively promote the uniform deposition of lithium ions and effectively inhibit the growth of dendrites, thereby extending the service life of lithium metal batteries; in addition, the functionalized coating also has many other advantages, such as light weight, good mechanical properties, and excellent thermal stability; the preparation method adopts an integrated preparation process, directly applies the functionalized intermediate coating on the surface of the copper foil, increases the bonding degree between the functionalized coating and the copper foil, and eliminates the step of bonding the functionalized coating to the current collector, which is convenient for large-scale production of energy storage monomers such as soft-pack batteries and button batteries, and the preparation process is convenient, fast and low-cost; compared with various existing commercial methods for improving battery cycle performance, the preparation method has greatly reduced costs, is suitable for large-scale commercial production, has broad application prospects, and helps to achieve a breakthrough in lithium metal batteries towards longer cycle life and higher coulomb efficiency.

[0023] 2. The polyethylene oxide used in the present invention is a polyether compound, and the ether oxygen group in its ethylene oxide unit can serve as an effective lithium-philic site, playing a guiding role in the uniform nucleation and growth of lithium ions.

[0024] 3. The bacterial cellulose used in the present invention is an unbranched polymer with nanofibrils produced by a bacterial community, which is composed of glucose units connected by β-glycosides. The fiber diameter of this material can reach the nanometer level, and it has excellent mechanical properties and good compatibility with polyethylene oxide. It also has a series of advantages such as high purity, non-toxic and environmentally friendly, degradable, and good hydrophilicity, and is widely used in the fields of food additives, sound equipment, textile industry, adsorption materials, fuel cells, etc. Therefore, mixing polyethylene oxide and bacterial cellulose can improve the mechanical strength of polyethylene oxide, and ultra-thin thickness can be achieved by blending its aqueous solution.

[0025] 4. The magnetic stirring method of the present invention has a flexible stirring speed and high efficiency. The magnetic particles are driven to rotate by the attraction between the magnetic particles and the chassis to achieve the stirring effect on polyethylene oxide and bacterial cellulose, avoiding the influence of impurities that may be introduced by traditional stirring methods, making the solution mixing more uniform and efficient, and the mixing process cleaner and pollution-free.

[0026] 5. The present invention adopts a blast oven for drying, and its high temperature environment can accelerate the volatilization of deionized water, and adopts a vacuum oven for combined drying, and its high temperature vacuum environment can further dry it under the condition of isolating it from the outside air. The whole drying process is fast and safe, and the influence of moisture, oxygen, etc. in the air on the preparation of the functionalized coating is avoided.

[0027] 6. The present invention achieves flexible control of the different thicknesses of the functionalized coating by using scrapers of different thicknesses.

[0028] In summary, the method of the present invention has simple process and low cost, and achieves the purpose of improving the cycle life and safety of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the preparation of the functionalized coating of the present invention.

[0030] Figure 2 This is a battery performance diagram obtained by performing a cyclic charge and discharge test using Example 2. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The bacterial cellulose has excellent mechanical strength, plays an important role in reducing the thickness of the functionalized coating, and has good biodegradability, is non-toxic and harmless, does not pollute the environment, and is an excellent material that meets the goal of sustainable development. The present invention mainly addresses the defects of lithium-ion batteries, uses a casting method to add polyethylene oxide and bacterial cellulose to deionized water to form a functionalized coating of polyethylene oxide and bacterial cellulose, and applies the functionalized coating on a copper foil to form a functionalized coating; the functionalized coating is used to regulate the deposition of lithium ions to make them uniformly nucleated and grown. The preparation process of the method is fast and simple, and the cost is low.

[0033] A functionalized coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water, wherein the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is (0.5-10): (5-60): (80-120) or (3-4): (15-20): (100-110).

[0034] The coating is simple to prepare, has a short production cycle, is easy to mass produce, and has broad prospects in commercial applications. Among them, polyethylene oxide contains ether oxygen bonds with negative potential, which are easy to form complex coordination with lithium ions with positive potential in the electrolyte, and polyethylene oxide is a safe and non-toxic polymer with good compatibility with deionized water. Bacterial cellulose has a cellulose purity of up to 95%, and is composed of microfibers with a diameter of 3 to 4 nanometers combined into fiber bundles with a thickness of 40 to 60 nanometers, which are interwoven to form a developed ultra-fine network structure. This structure gives it excellent mechanical properties, and bacterial cellulose has good biodegradability and is pollution-free to the environment.

[0035] The present invention provides a method for preparing a functionalized coating for improving battery cycle performance, comprising the following steps:

[0036] Step 1, using a vacuum oven to dry the polyethylene oxide, the vacuum oven temperature is set to 60° C.-65° C., and the drying time is 15-30 hours;

[0037] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer, the magnetic stirring rate is 300-600 rpm, the stirring time is 18-30 hours, so that the solution is mixed evenly to obtain a functional coating of polyethylene oxide and bacterial cellulose; according to the mass ratio, polyethylene oxide: bacterial cellulose: deionized water = (0.5-10): (5-60): (80-120) or (3-4): (15-20): (100-110).

[0038] like Figure 1 As shown, the present invention also provides an application of a functional coating for improving the cycle performance of a battery. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated with a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 50 to 400 μm to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 60 to 80°C for 10 to 30 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 60 to 80°C for 18 to 30 hours to completely volatilize the moisture inside, thereby obtaining an electrode coated with a polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 0.1 to 6 μm.

[0039] In order to make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. The components of the embodiment of the present invention described and shown in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiment of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiment of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0040] Example 1

[0041] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 0.5:5:80.

[0042] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0043] Step 1, using a vacuum oven to dry the polyethylene oxide, the vacuum oven temperature is set to 60° C., and the drying time is 30 hours;

[0044] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer at a magnetic stirring rate of 300 rpm for 30 hours to mix the solution evenly to obtain a functionalized coating of polyethylene oxide and bacterial cellulose; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 0.5:5:80.

[0045] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 50 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 60°C for 30 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 60°C for 30 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 0.2 μm.

[0046] Example 2

[0047] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water, wherein the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is 5:10:100.

[0048] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0049] Step 1, using a vacuum oven to dry the polyethylene oxide, the vacuum oven temperature is set to 60° C., and the drying time is 26 hours;

[0050] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer at a magnetic stirring rate of 300 rpm for 30 hours to mix the solution evenly to obtain a functionalized coating of polyethylene oxide and bacterial cellulose; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 5:10:100.

[0051] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 100 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 65°C for 24 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 65°C for 26 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 1 μm.

[0052] Example 3

[0053] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water, wherein the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is 5:20:100.

[0054] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0055] Step 1, drying the polyethylene oxide in a vacuum oven, the vacuum oven temperature is set to 62° C., and the drying time is 24 hours;

[0056] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer at a rate of 400 rpm for 24 hours to mix the solution evenly to obtain a functionalized coating of polyethylene oxide and bacterial cellulose; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 5:20:100.

[0057] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 150 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 70°C for 20 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 70°C for 24 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 1.6 μm.

[0058] Example 4

[0059] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water, wherein the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is 5:30:120.

[0060] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0061] Step 1, using a vacuum oven to dry the polyethylene oxide, the vacuum oven temperature is set to 62° C., and the drying time is 20 hours;

[0062] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer at a rate of 400 rpm for 24 hours to mix the solution evenly to obtain a functionalized coating of polyethylene oxide and bacterial cellulose; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 5:30:120.

[0063] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 200 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 75°C for 18 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 75°C for 20 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 2.5 μm.

[0064] Example 5

[0065] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water, wherein the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is 10:20:120.

[0066] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0067] Step 1, using a vacuum oven to dry the polyethylene oxide, the vacuum oven temperature is set to 65° C., and the drying time is 18 hours;

[0068] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer at a rate of 500 rpm for 18 hours to mix the solution evenly to obtain a functionalized coating of polyethylene oxide and bacterial cellulose; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 10:20:120.

[0069] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 300 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 78°C for 15 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 78°C for 20 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 4 μm.

[0070] Example 6

[0071] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water, wherein the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is 10:30:120.

[0072] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0073] Step 1, drying the polyethylene oxide in a vacuum oven, the vacuum oven temperature is set to 65° C., and the drying time is 15 hours;

[0074] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer, the magnetic stirring rate is 500 rpm, the stirring time is 18 hours, so that the solution is mixed evenly to obtain a functional coating of polyethylene oxide and bacterial cellulose; according to the mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 10:30:120.

[0075] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 200 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 75°C for 18 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 75°C for 20 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 2.5 μm.

[0076] Example 7

[0077] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water, wherein the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is 3:15:100.

[0078] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0079] Step 1, drying the polyethylene oxide in a vacuum oven, the vacuum oven temperature is set to 60° C., and the drying time is 24 hours;

[0080] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer at a rate of 450 rpm for 24 hours to mix the solution evenly to obtain a functional coating of polyethylene oxide and bacterial cellulose; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 3:15:100.

[0081] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 200 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 75°C for 18 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 75°C for 20 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 2.5 μm.

[0082] Example 8

[0083] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water, wherein the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is 3.5:17:105.

[0084] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0085] Step 1, drying the polyethylene oxide in a vacuum oven, the vacuum oven temperature is set to 62° C., and the drying time is 24 hours;

[0086] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer at a rate of 500 rpm for 20 hours to mix the solution evenly to obtain a functional coating of polyethylene oxide and bacterial cellulose; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 3.5:17:105.

[0087] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 300 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 70°C for 15 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 70°C for 24 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 4 μm.

[0088] Example 9

[0089] A functional coating for improving battery cycle performance comprises polyethylene oxide, bacterial cellulose and deionized water, wherein the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is 4:20:110.

[0090] A method for preparing a functionalized coating for improving battery cycle performance comprises the following steps:

[0091] Step 1, drying the polyethylene oxide in a vacuum oven, the vacuum oven temperature is set to 65° C., and the drying time is 24 hours;

[0092] Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer at a rate of 550 rpm for 18 hours to mix the solution evenly to obtain a functionalized coating of polyethylene oxide and bacterial cellulose; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 4:20:110.

[0093] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 150 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 60°C for 28 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 60°C for 30 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 1.6 μm.

[0094] A functional coating for improving battery cycle performance is used. In a dry atmosphere, the functional coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil by a casting method, and is evenly coated by a scraper, wherein the functional coating is controlled by adjusting the thickness of the scraper, and the thickness of the scraper is 400 μm, so as to form a functional coating; then the copper foil coated with the functional coating is placed in a blast oven and dried at a temperature of 80°C for 12 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 80°C for 18 hours to completely volatilize the water inside, so as to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functional coating, wherein the thickness of the functional coating is 6 μm.

[0095] Control example: The electrode without functional coating was used as the positive electrode, the metal lithium was used as the negative electrode, the separator was a commercial polypropylene microporous separator, 60 μL of commercial LiPF6 electrolyte was added to assemble a half-cell, and the electrolyte was charged at 1 mA / cm 2 The battery performance is shown in the following table. Figure 2 As shown, the Coulomb efficiency decays significantly after about 250 stable cycles.

[0096] The functionalized coating of polyethylene oxide and bacterial cellulose prepared in Example 2 was coated on the copper foil by the application method of the present invention. The electrode integrated with the copper foil was used as the positive electrode, the metal lithium was used as the negative electrode, and the diaphragm was a commercial polypropylene microporous diaphragm. 60 μL of commercial LiPF6 electrolyte was added dropwise to assemble a half-cell. 2 The battery performance is shown in the following table. Figure 2 As shown, after 400 stable cycles, the coulombic efficiency can still maintain 97.43%, indicating that the polyethylene oxide and bacterial cellulose integrated copper foil can induce lithium ions to deposit evenly and effectively inhibit the growth of lithium dendrites, and the battery cycle performance has been greatly improved. Compared with the half-cell assembled from the copper foil without the functional coating of the present invention, when the battery runs to the 250th cycle, the coulombic efficiency of the battery is increased by 6%, and when the battery runs to the 400th cycle, the coulombic efficiency can be maintained at 98.4%, while the coulombic efficiency of the battery without the functional coating has declined to 30.1% at the 335th cycle.

[0097] The mixed solution of polyethylene oxide and bacterial cellulose is applied to the copper foil by the tape casting method, and the coating is evenly spread by a scraper, and then the copper foil is placed in an oven to completely volatilize the internal water, thereby obtaining an integrated electrode of polyethylene oxide, bacterial cellulose and copper foil, which achieves a good effect of inducing uniform deposition of lithium ions and inhibiting lithium dendrites, greatly improving the cycle performance of the battery. At the same time, the preparation process is simple, fast and low-cost. The thickness and performance of the functionalized intermediate layer can be flexibly controlled by controlling the content of bacterial cellulose and the thickness of the scraper, thereby preparing a lithium metal battery with higher cycle stability. At the same time, the preparation method of the functionalized coating for improving the cycle performance of the battery can also be used in other batteries such as lithium-sulfur batteries, solid-state batteries and air batteries, so that the cycle stability can be further improved, showing a wide range of application prospects.

[0098] In summary, the present invention is a method for preparing a functionalized coating for improving battery cycle performance. The preparation process is simple, fast, low-cost, suitable for large-scale production, and can effectively induce uniform deposition of lithium ions, inhibit lithium dendrites, and greatly improve battery cycle stability.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A functionalized coating for improving battery cycle performance, characterized in that: It comprises polyethylene oxide, bacterial cellulose and deionized water; according to the mass ratio, polyethylene oxide: bacterial cellulose: deionized water = (0.5-10): (5-60): (80-120).

2. A functionalized coating for improving battery cycle performance, characterized in that: It includes polyethylene oxide, bacterial cellulose and deionized water; according to the mass ratio, polyethylene oxide: bacterial cellulose: deionized water = (3-4): (15-20): (100-110).

3. A method for preparing a functionalized coating for improving battery cycle performance, characterized in that: The following steps are involved: Step 1, drying the polyethylene oxide; Step 2: adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring to mix the solution evenly to obtain a functional coating of polyethylene oxide and bacterial cellulose.

4. The method for preparing a functionalized coating for improving battery cycle performance according to claim 3, characterized in that: The step 1 is specifically as follows: The polyethylene oxide is dried in a vacuum oven, the temperature of the vacuum oven is set at 60°C-65°C, and the drying time is 18-26 hours.

5. The method for preparing a functionalized coating for improving battery cycle performance according to claim 3, characterized in that: In the step 2, the mass ratio of polyethylene oxide: bacterial cellulose: deionized water is (0.5-10): (5-60): (80-120) or (3-4): (15-20): (100-110).

6. The method for preparing a functionalized coating for improving battery cycle performance according to claim 3, characterized in that: In the step 2, a magnetic stirrer is used for stirring, the magnetic stirring rate is 300-600 rpm, and the stirring time is 18-30 hours.

7. The method for preparing a functionalized coating for improving battery cycle performance according to claim 3, characterized in that: The functional coating comprises polyethylene oxide, bacterial cellulose and deionized water; the weight ratio of polyethylene oxide: bacterial cellulose: deionized water is 5:10:100; and the preparation method comprises the following steps: Step 1, drying the polyethylene oxide in a vacuum oven, the vacuum oven temperature is set to 60° C., and the drying time is 26 hours; Step 2, adding the polyethylene oxide and bacterial cellulose dried in step 1 into deionized water, and stirring with a magnetic stirrer at a magnetic stirring rate of 300 rpm for 30 hours to mix the solution evenly to obtain a functionalized coating of polyethylene oxide and bacterial cellulose; in terms of mass ratio, polyethylene oxide: bacterial cellulose: deionized water = 5:10:

100.

8. An application of a functionalized coating for improving battery cycle performance, characterized in that: In a dry atmosphere, the functionalized coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on the copper foil, and is evenly coated with a scraper to form a functionalized coating; the copper foil coated with the functionalized coating is placed in a blast oven and a vacuum oven in turn for drying to obtain an electrode coated with the polyethylene oxide and bacterial cellulose functionalized coating.

9. The use of a functional coating for improving battery cycle performance according to claim 8, characterized in that: In a dry atmosphere, the functionalized coating of polyethylene oxide and bacterial cellulose obtained in step 2 is placed on a copper foil, and is evenly coated with a scraper, wherein the thickness of the scraper is 50-400 μm, to form a functionalized coating; the copper foil coated with the functionalized coating is placed in a blast oven and dried at a temperature of 60-80° C. for 10-30 minutes, taken out, and transferred to a vacuum oven and continued to be dried at a temperature of 60-80° C. for 18-26 hours to obtain an electrode coated with a polyethylene oxide and bacterial cellulose functionalized coating, wherein the thickness of the functionalized coating is 0.1-6 μm.

10. A battery comprising an electrode, characterized in that: The electrode is an electrode coated with the polyethylene oxide and bacterial cellulose functional coating according to any one of claims 1 to 2 or an electrode coated with the polyethylene oxide and bacterial cellulose functional coating prepared by the method according to any one of claims 3 to 7.

Citation Information

Patent Citations

  • Water-based bacterial cellulose paint for lithium battery diaphragms

    CN104479464A

  • Preparation method of metal lithium negative electrode protective layer material

    CN110600739A

  • Preparation method and application of nano bacterial cellulose / polyoxyethylene composite solid electrolyte

    CN111969246A

  • Low-moisture coating slurry, coating diaphragm and preparation method thereof

    CN116417756A

  • KR20190068065A